Sozialisierte Metaphysik - Daniel Burnfin (Recherches Germaniques)
This article discusses and contrasts two accounts of the meaning of ‘abstraction’. First it discusses the approach and problems of the more conventional account, according to which abstraction is a cognitive derivation of generalities. Then it discusses the unconventional account of Alfred Sohn-Rethel, which can serve as an alternative to the conventional account and which avoids the problems it raises.